Revitalisasi REVITALISASI TRADISI TIRAKATAN UNTUK PENGUATAN NILAI KEBANGSAAN MELALUI KOLABORASI PERGURUAN TINGGI DAN MASYARAKAT DI DESA JANTI, WARU, SIDOARJO. - Atmari Atmari; Sudja’i Sudja’i; Pingki Aurel Laisyah; Dini Rachmawati (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service study aims to strengthen national values through the revitalization of the Tirakatan tradition by fostering collaboration between universities and the community in Desa Janti, Waru, Sidoarjo. The program involved 52 participants, including youth and local community leaders. The method used is a participatory collaborative approach, covering mapping of local cultural potential, program socialization, local facilitator training, implementation of Tirakatan, and reflection on national values. The results indicate that Tirakatan is an effective medium for character education, enhancing participants’ understanding of patriotism, solidarity, appreciation of history, and cultural preservation. Collaboration between universities and the community creates a contextual, interactive, and meaningful learning experience. The findings recommend developing similar programs to make local traditions a collective movement to strengthen the national spirit.